(untitled) (Plant Tissue Culture and Biotechnology, 2023)
Abiotic stresses like salinity, water stress, high light intensity, heavy metals, etc. have a significant influence on the morphology, biochemical characteristics, and crop productivity, of Brassica species. Among these numerous abiotic stresses, stress from salinity is a significant issue, that demands immediate attention and resolution. Therefore, in this study, the tolerance of Brassica carinata and five different varieties of Brassica campestris including Agrani, Shafal, BINA Sharisha-6, BARI Sharisha-15 and Tori-7 were examined at varying concentrations of NaCl (0, 50, 100, 150, 200 mM). Different morpho-physiological and biochemical properties including seed germination parameters, root/shoot ratio, proline content, H2O2 and MDA level, photosynthetic pigments, and Na+/K+ ion accumulation were measured and showed varying responses to the inhibitory impacts of NaCl. B. carinata, BINA Sharisha-6, Tori-7 and Shafal, with increasing NaCl concentrations resulted in the loss of germination percentages, root/shoot ratio, levels of photosynthetic pigments, proline, levels of H2O2 and MDA and the Na+/K+ ion accumulation in comparison to the other Brassica varieties. Among these varieties, Shafal, showed the lowest values of the salt tolerant indicators. In contrast, variety Agrani and BARI Sharisha-15 exhibited high proline content, a good level of H2O2 and MDA and photosynthetic pigments, in response to salt stress, which enhanced their hydration status, enzyme activities and cellular functions. Plant Tissue Cult. & Biotech. 33(2): 167-180, 2023 (December)